Identification of Nucleus Pulposus Precursor Cells and Notochordal Remnants in the Mouse: Implications for Disk Degeneration and Chordoma Formation - Choi, Kyung-Suk (2008)
A classically identified “notochordal” cell population in the nucleus pulposus is thought to regulate disk homeostasis. However, the embryonic origin of these cells has been under dispute for >60 years. Here we provide the first direct evidence that all cell types in the adult mouse nucleus pulposus are derived from the embryonic notochord. Additionally, rare isolated embryonic notochord cells remained in the vertebral column and resembled “notochordal remnants,” which in humans have been proposed to give rise to a rare type of late-onset cancer called chordoma. Previously, this cell type had not been identified in the mouse model system. The development and characterization of a mouse model that can be used to fate map nucleus pulposus precursor cells in any mutant background will be useful for uncovering the cellular and molecular mechanisms of disk degeneration. In addition, the identification of notochordal remnants in mice is the first step towards generating an in vivo model of chordoma.